HADIS PENDIDIKAN : PENELUSURAN AKAR PENDIDIKAN JASMANI DALAM HADIS - Lazuardi, Lazuardi (FORUM PAEDAGOGIK, 2014)
Physical education is an integral part of the overall education. Generally, this type of education always be integrated with physical education and health. Physical education is not only related with physical development but is closely connected with the spiritual and mental health. A popular saying proves it "in a healthy body there is a healthy and strong spirit" that "matched" with the Arabic phrase al aqlu al salim fi al jism al salim.Physical education aims to develop aspects of physical fitness, motor skills, discipline, in addition to the physical education can also develop social skills, critical reasoning, emotional stability, moral action and aspects of a healthy lifestyle. All the goals will be achieved through training and physical activity (exercise) which is continuous and regular planned. Physical training plays an important role in improving physical fitness. Physical fitness will determine the person's physical ability to perform daily activities. Daily activities will run smoothly and can be accomplished either by physically healthy, fit, and productive.